Study of Effect of Concentration of MnCl2 Solution on Intensity of VCD chip Spectrometer Imagery - Lailatin Nuriyah; S. J. Iswarin; Gancang Saroja (Natural B, Journal of Health and Environmental Sciences, 2015)
Spectroscopy is study of interaction between radiation of wave and matter. In its application, spectroscopy has been used to observe and study the characteristics of a matter through its resulted spectrums. In this research, spectrometer was built with VCD chip and two kind of lamp sources, incandescent and fluorescent lamp. The MnCl2 solutions with concentration 0, 1, 2, and 3 M were used as sample. Image-J software was used to analysis the resulted spectrums. The results showed an interaction between rays and the solution with indication the image intensity decreased.